Percutaneous Microcoil Localization of a Small, Totally Endophytic Renal Mass for Nephron-Sparing Surgery: A Case Report and Literature Review - Su, Tianhao; Zhang, Zhiyuan; Zhao, Meishan; Hao, Gangyue; Tian, Ye; Jin, Long (Frontiers in Oncology, 2022)
Small, totally endophytic renal masses present a technical challenge for surgical extirpation due to poor identifiability during surgery. The method for the precise localization of totally endophytic tumours before nephron-sparing surgery could be optimized. An asymptomatic 70-year-old male presented with a right-sided, 16-mm, totally endophytic renal mass on computed tomography (CT). CT-guided percutaneous microcoil localization was carried out prior to laparoscopy to provide a direction for partial nephrectomy. During the 25 minutes of the localization procedure, the patient underwent five local CT scans, and his cumulative effective radiation dosage was 5.1 mSv. The span between localization and the start of the operation was 15 hours. The laparoscopic operation time was 105 minutes, and the ischaemia time was 25 minutes. The postoperative recovery was smooth, and no perioperative complications occurred. Pathology showed the mass to be renal clear cell carcinoma, WHO/ISUP grade 2, with a 2-mm, clear surgical margin. The patient remained free of recurrence on follow-up for eleven months. To our knowledge, this application of microcoil implantation prior to laparoscopic partial nephrectomy towards an intrarenal mass could be an early reported attempt for the localized method applied in renal surgery. The percutaneous microcoil localization of endophytic renal tumours is potentially safe and effective prior to laparoscopic partial nephrectomy.